2005
DOI: 10.1124/jpet.105.086124
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Prostaglandin Transport and Metabolism Augment Protease-Activated Receptor-2-Mediated Increases in Prostaglandin E2 Levels and Smooth Muscle Relaxation in Mouse Isolated Trachea

Abstract: Stimulants of protease-activated receptor-2 (PAR 2 ), such as Ser-Leu-Ile-Gly-Arg-Leu-NH 2 (SLIGRL), cause airway smooth muscle relaxation via the release of the bronchodilatory prostanoid prostaglandin E 2 (PGE 2 ). The principal aim of the current study was to determine whether compounds that inhibit PGE 2 reuptake by the prostaglandin transporter [bromocresol green and U46619 (9,11-dideoxy-9␣,11␣-methanoepoxy PGF2␣) and PGE 2 metabolism by 15-hydroxyprostaglandin dehydrogenase (thiazolidenedione compounds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 30 publications
(40 reference statements)
3
30
2
Order By: Relevance
“…We found that the effects of RGZ were additive, with the partial relaxation achieved in the presence of a maximally effective concentration of ALB. This finding contrasts with a single study in mouse trachea, where ISO-mediated relaxation was not increased in the presence of RGZ despite a modest dilation seen with RGZ alone (17). However, these contrasting results have been obtained under different experimental conditions, measuring either ORIGINAL RESEARCH changes in area of small airways in perfused lung slices or changes in force in trachea under static conditions.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…We found that the effects of RGZ were additive, with the partial relaxation achieved in the presence of a maximally effective concentration of ALB. This finding contrasts with a single study in mouse trachea, where ISO-mediated relaxation was not increased in the presence of RGZ despite a modest dilation seen with RGZ alone (17). However, these contrasting results have been obtained under different experimental conditions, measuring either ORIGINAL RESEARCH changes in area of small airways in perfused lung slices or changes in force in trachea under static conditions.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, dilator responses to RGZ were maintained in the presence of validated effective concentrations of indomethacin or NOLA (17,31). These findings allowed us to exclude the possible contributions of cAMP or epithelial-derived relaxing factors such as PGE 2 or NO to RGZ-mediated relaxation of small airways in perfused lung slices.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In BALB/c mice, treatment with either RGZ or CGZ inhibited OVA-induced airway inflammation and fibrosis as well as the development of AHR (14,32,35), with the effects of the synthetic PPAR␥ ligands mimicked by AdPPAR␥ (15, 17) and abrogated by GW9662 (14,15,17,35). Although RGZ also reduced the development of AHR in OVA-challenged C57BL/6 mice, the increase in BAL inflammatory cells in this mouse strain was not affected, suggesting that RGZ may also modulate AHR by a mechanism that is independent of inhibition of inflammatory cell recruitment to the airway (33).In addition to these inhibitory effects in models of chronic AAD, RGZ has been shown to elicit acute relaxation of mouse tracheal segments and intrapulmonary airways in precision cut lung slices (PCLS) precontracted with muscarinic agonists in vitro (3,12). In PCLS, RGZ elicited complete relaxation under conditions of impaired ␤-adrenoceptor agonist responsiveness, opposing contraction by inhibiting calcium oscillations and sensitivity (3).…”
mentioning
confidence: 99%